Skin cancer preventative behaviors in state park workers: a pilot study - Nahar, Vinayak K. (Environ Health Prev Med, 2014)
OBJECTIVES: Considering the potential for occupational sun exposure among state park workers, the purpose of this pilot study was to identify skin cancer knowledge, health beliefs, self-efficacy, and sun protection behaviors (SPBs) among state park employees. METHODS: The current study used a cross-sectional survey research design with state park workers in a Southern state. Of the 94 possible employees who could have participated in the study, 87 completed the survey. RESULTS: Assessment of the participants’ skin cancer knowledge demonstrated an average correct response rate of 68.8 %. While the vast majority (87.4 %) believed that skin cancer is a serious disease, a minority (42.5 %) believed they would develop skin cancer sometime during their lifetime, and even fewer (35.6 %) believed their risk was higher than average. Collectively, workers reported low levels of SPBs. The most commonly reported barriers to sun protection were “inconvenient,” “too hot to wear,” and “forget to protect.” Half of the participants (50.6 %) were highly confident in their ability to wear long pants while in the sun. About the same proportion of participants was highly confident they could wear a wide-brimmed hat (21.8 %) and sunscreen (20.7 %). CONCLUSIONS: Based on available evidence, a need exists to develop individual and worksite programs and interventions to increase skin cancer prevention behaviors among this occupational group. This data could serve as a baseline to monitor and evaluate the efficacy of these interventions.